1998
DOI: 10.1021/es9711324
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Diffusion Coefficients in Low-Permeability Porous Media Using a Macropore Column

Abstract: Diffusion coefficients in an aquitard material were measured by conducting miscible solute transport experiments through a specially constructed macropore column. Stainless steel HPLC columns were prepared in a manner that created an annular region of repacked aquitard material and a central core of medium-grained quartz sand. The column transport approach minimizes volatilization and sorption losses that can be problematic when measuring hydrophobic organic chemical diffusion with diffusion-cell methods or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 34 publications
(45 reference statements)
2
39
0
Order By: Relevance
“…A question of great interest is the compatibility of these two techniques. Good agreement between the results of the two techniques has been reported (Nkedi-Kizza and others 1987; Lee and others 1988;MacIntyre and others 1991;Spurlock and others 1995;Young and Ball 1998). In contrast, several investigators have observed that batch-determined distribution coef®cients are higher than their MD counterparts (Bilkert and Rao 1985;Bouchard and others 1988;MacIntyre and Stauffer 1988;Celorie and others 1989;Lion and others 1990;Piatt and others 1996;Maraqa and others 1998;Carmichael and others 1999;Thomsen and others 1999;Kim and others 2000).…”
Section: Introductionmentioning
confidence: 63%
“…A question of great interest is the compatibility of these two techniques. Good agreement between the results of the two techniques has been reported (Nkedi-Kizza and others 1987; Lee and others 1988;MacIntyre and others 1991;Spurlock and others 1995;Young and Ball 1998). In contrast, several investigators have observed that batch-determined distribution coef®cients are higher than their MD counterparts (Bilkert and Rao 1985;Bouchard and others 1988;MacIntyre and Stauffer 1988;Celorie and others 1989;Lion and others 1990;Piatt and others 1996;Maraqa and others 1998;Carmichael and others 1999;Thomsen and others 1999;Kim and others 2000).…”
Section: Introductionmentioning
confidence: 63%
“…The model could be used to explain the transfer mechanisms that increased leaching by 20% in an intermittent (as compared to continuous) flow regime (Cote et al, 1999). In a cylindrical macropore system, a MIM with diffusion equation could be used to determine the effective diffusion coefficient of soil surrounding a sand filled macropore (Young and Ball, 1998 Ahuja et al (1995) used RZWQM to study transport of a surface-applied Br − tracer under rainfall in a soil column with a 3-mm artificial macropore. A good match of the rapid Br − breakthrough resulted when the macropore water was assumed to mix with only 0.5 mm of matrix solution, revealing restricted solute transfer through the compacted macropore walls (Ahuja et al, 1995).…”
Section: Modelling Of Tracer Transport In Preferential Flow Systemsmentioning
confidence: 99%
“…Effective diffusion coefficients are defined as molecular diffusivity divided by an effective tortuosity factor, as described elsewhere [Ball et al, 1997a;Young and Ball, 1998]. L is the thickness of the first layer (OSCL) and is a function of the coring location, x is distance from the interface between the aquifer and aquitard, and t is time.…”
Section: Modelmentioning
confidence: 99%